Homosexuality: A Mental Problem that Shouldn't Be Called Sexual Deviance - Abdulaziz Daftari; Ali Khaleghi (Iranian Journal of Psychiatry, 2025)
Homosexuality is a sexual orientation that is the subject of much debate and has various supporters and opponents, and for this reason, there are different approaches to it. Some view homosexuality from a moral perspective, while others view it from the perspective of individual freedom and choice. Some governments fully support it and have implemented strong protective laws for homosexuality, while some countries are completely against it. In addition, there is also a variety of scientific evidence surrounding homosexuality: from evidence indicating a different biology of homosexuals to evidence that refutes the biological and neurological correlates of homosexuality. Experts in the fields of humanities such as philosophy and religious sciences have also raised different debates in this regard. Therefore, in this editorial, our goal was to provide a brief description of homosexuality from the perspectives of biology and neuroscience, psychology and psychiatry, philosophy, and various religions.